Tasmim al-Taqwim al-Syumuli Fi Ta’lim al-Muthala’ah - Rini, Rini; Harahap, Partomuan (Institut Agama Islam Negeri Curup, 2021)
The purpose of this article is to design the holistic evaluation in teaching reading. Assessment plays an important role in education process. Good evaluation is essential for good education and good learning. The evaluation of reading material is able to depict the faults and advantages of a reading instruction program. Also, students are able to know the level of their ability and absorption of reading materials from the assessment. The research method used is the library method. Assessment is an important part of teaching reading. So far, there are still found some designs of reading assessment which are not integrated and comprehensive, identical to the theory of reading comprehension including literal reading, interpretive reading, critical reading, and creative reading. As a result of this research, the design of the reading assessment is based upon the teaching and learning process (the daily calendar) or the so-called formative evaluation and an evaluation that is based at the end of the lecture in the form of midterm exams and final exams, or what is called a final evaluation. The evaluation design has two types comprising the practice evaluation and the written evaluation.